Long‐term mean changes in actual evapotranspiration over China under climate warming and the attribution analysis within the Budyko framework. (28th July 2021) - Su, Tao; Feng, Taichen; Huang, Bicheng; Han, Zixuan; Qian, Zhonghua; Feng, Guolin; Hou, Wei; Dong, Wenjie
Abstract: In this study, the temporal variation of actual evapotranspiration (AE) over China during 1980–2015 is analysed based on an ensemble of six reanalyses and a complementary‐relationship‐based AE dataset. The results reveal that annual mean AE in China increases significantly, and the major regime shift occurred around 1998. Accordingly, long‐term mean AE changes from 1999–2015 relative to 1980–1997 are computed to quantify the spatial pattern of AE trends. In general, annual AE increases significantly in southern and northwestern China but decreases significantly in northeastern China and eastern Tibetan Plateau. Then we examine the primary cause for changes in AE using the Budyko framework, in which the change of climate is represented by changes in precipitation and potential evapotranspiration and the shift in landscape characteristics is represented by the parameter n . Overall, increasing potential evapotranspiration is the main contributor to the increase of AE in southeastern China. Increasing potential evapotranspiration and the parameter n are the main contributors to the increase of AE in southwestern China. Decreasing AE in northeastern China and eastern Tibetan Plateau are respectively caused by changes in precipitation and the parameter n, whereas the combination of these two factors has led to increasing AE in northwestern China. It is shown here that the contribution of the parameter n is comparable to that of climate change in western China. A positive correlation is found between vegetation coverage and the parameter n ; however, vegetation type, catchment slope, irrigation practices, and glacial meltwater also have an impact on regional n . A concurrent occurrence of the negative contribution of parameter n and positive vegetation coverage change is found in the forest land of northeastern and southeastern China. Decreasing irrigation water is likely the main reason for the negative contribution of n in cropland of the North China Plain. Abstract : Annual mean actual evapotranspiration (AE) in China increases significantly from 1980 to 2015, and the major regime shift occurred around 1998. Long‐term mean AE changes from 1999–2015 relative to 1980–1997 are computed to quantify the spatial pattern of AE trends. Increasing potential evapotranspiration is the main contributor to increasing AE in southeastern China. Increasing potential evapotranspiration and the parameter n are the main contributors to increasing AE in southwestern China. Decreasing AE in northeastern China and eastern Tibetan Plateau are respectively caused by changes in precipitation and the parameter n, whereas the combination of these two factors has led to increasing AE in northwestern China.